(untitled) (Bioscience Journal, 2016)
The disruption of the delicate balance between the generation of reactive oxygen species (ROS) and antioxidant scavenging systems can lead to many health problems. Polysaccharides extracted from fungi fruit body and myceliums have several potential health benefits. In this study, the antioxidant capacity and cell protective effects of a polysaccharide isolated from Lentinus edodes mycelia (LMP) were investigated. The antioxidant properties of LMP were screened using radical scavenging (1, 1-diphenyl-2-picrylhydrazyl (DPPH), hydroxyl, and superoxide anion), reducing power and inhibition of lipid peroxidation assays. Intracellular reactive oxygen species (ROS), in response to H2O2, was determined by the dichloro-dihydro-fluorescein diacetate (DCFH-DA) assay. Rat insulinoma (INS-1) cells apoptosis was detected using flow cytometry analysis. The results showed that LMP exhibited significantly strong radical scavenging activity. At the concentration of 2.0 mg mL-1, DPPH radical, hydroxyl radical, and superoxide anion radical scavenging rates are 80.32 ± 2.58%, 92.56 ± 3.11% and 93.73 ± 2.82%, respectively. The reducing power and inhibition of lipid peroxidation activity of LMP were as strong as the positive control. LMP alleviated the intracellular reactive oxygen species level and inhibited islet cell apoptosis significantly. The results open perspectives for studies of LMP in the treatment of diabetes.